European Stroke Organisation (ESO) Guidelines on Moyamoya angiopathy Endorsed by Vascular European Reference Network (VASCERN). (March 2023) - Bersano, Anna; Khan, Nadia; Fuentes, Blanca; Acerbi, Francesco; Canavero, Isabella; Tournier-Lasserve, Elisabeth; Vajcoczy, Peter; Zedde, Maria Luisa; Hussain, Salman; Lémeret, Sabrina; Kraemer, Markus; Herve, Dominique
The European Stroke Organisation (ESO) guidelines on Moyamoya Angiopathy (MMA), developed according to ESO standard operating procedure and Grading of Recommendations, Assessment, Development and Evaluation (GRADE) methodology, were compiled to assist clinicians in managing patients with MMA in their decision making. A working group involving neurologists, neurosurgeons, a geneticist and methodologists identified nine relevant clinical questions, performed systematic literature reviews and, whenever possible, meta-analyses. Quality assessment of the available evidence was made with specific recommendations. In the absence of sufficient evidence to provide recommendations, Expert Consensus Statements were formulated. Based on low quality evidence from one RCT, we recommend direct bypass surgery in adult patients with haemorrhagic presentation. For ischaemic adult patients and children, we suggest revascularization surgery using direct or combined technique rather than indirect, in the presence of haemodynamic impairment and with an interval of 6–12 weeks between the last cerebrovascular event and surgery. In the absence of robust trial, an Expert Consensus was reached recommending long-term antiplatelet therapy in non-haemorrhagic MMA, as it may reduce risk of embolic stroke. We also agreed on the utility of performing pre- and post- operative haemodynamic and posterior cerebral artery assessment. There were insufficient data to recommend systematic variant screening of RNF213 p.R4810K. Additionally, we suggest that long-term MMA neuroimaging follow up may guide therapeutic decision making by assessing the disease progression. We believe that this guideline, which is the first comprehensive European guideline on MMA management using GRADE methods will assist clinicians to choose the most effective management strategy for MMA.